A cross‐sectional description of the health characteristics of cognitively impaired older adults. (5th November 2022) - Merrick, Eamon; Shannon, Kay; Neville, Stephen; Bail, Kasia; Vorster, Anja; Fry, Margaret
Abstract: Objectives: The analysis presented here describes the care needs of older adults with and without cognitive impairment. To describe the health characteristics of older adults with and without cognitive impairment who receive home care or Aged Residential Care services in New Zealand. Methods: A descriptive analysis of the initial interRAI assessment for adults older than 55 years was undertaken. Data were grouped by level of assessed cognitive impairment. The population proportions for each level of the following scales were calculated: Changes in Health, End‐stage Disease, Signs, and Symptoms Scale (CHESS), pain, pressure injury risk, Activities of Daily Living (ADL), depression screening, and body mass index (BMI). Results: The analysis included 93, 680 assessments. The mean age was 83 years (SD = 8.7) a positive association was observed between age and cognitive impairment ( p < 0.01). People with cognitive impairment were less likely to have been recently hospitalised or to have attended ED ( p < 0.01). Significant associations with effect sizes ≥3 were observed for cognitive impairment and ADL ( p < 0.01, γ = 0.63), pain ( p < 0.01, γ = −0.32), and risk of pressure injury ( p < 0.01, Cramer's V = 0.271). Conclusions: The results reinforce a need to be alert to the differential care needs of older adults with moderate/severe cognitive impairment. The findings may act as a trigger for practitioners to focus assessment on aspects of care that, due to context, may otherwise be underassessed or untreated.